THE ATTRACTION OF FORENSIC ACCOUNTING: EXPLORING THE CHARACTERISTICS OF ENGAGED STUDENTS - Callahan, J.P.; Stevens, S.H. (Ayden International Journal of Banking, Finance and Technology, 2024)
The supply of well-prepared students for forensic accounting is low, largely due to the limited number of universities offering courses focused on forensic accounting. To understand the profile of a student interested in forensic accounting, a survey was conducted among college-aged students to determine what personal interests, educational experiences, and backgrounds correlate with an interest in forensic accounting. The study found that forensic accounting is interesting to students regardless of their major or interest in accounting, and there is much excitement and interest among students in forensic accounting, which could aid in recruiting students into forensic accounting courses. Additionally, the study identified types of background experiences or personality traits that correlate with an interest in forensic accounting. Finally, the study aimed to determine whether forensic accounting tasks and experiences are inherently interesting to students. The results offer exciting and positive news for the future of forensic accounting, as students desire more coursework in this field.